Estructura factorial de la escala “Falta de personal” en trabajadores de una empresa retail peruana - Andia Ventura, Mijail Epifanio (2021)
The present study aims to analyze the internal structure of the "Lack of Personnel" scale. Participants were 201 workers of both genders from the retail sector of a Peruvian company. The evaluation of the internal structure shows a better fit for the model of two correlated factors of the scale, "Lack of manpower" and "Lack of expertise", coinciding with the definition of the construct made by its creators, Hudson and Shen (2015). The reliability analysis was carried out through the internal consistency method, obtaining values of ω = .77 and ω = .78, respectively. In conclusion, the results show support for the theoretical structure of two correlated factors.